2019
DOI: 10.4102/sajip.v45i0.1588
|View full text |Cite
|
Sign up to set email alerts
|

Gender traits in relation to work versus career salience

Abstract: Orientation: The concepts of work- and career-role salience are used interchangeably, yet work focuses on the short-term aspect and career on the long-term aspect.Research purpose: We utilised gender traits, that is, masculinity, femininity and psychological androgyny, to find greater nuances in the salience of work versus career roles. We also set out to confirm the adapted factor structure of the revised Bem Sex Role Inventory (BSRI).Motivation for the study: Generally, self-reported sex is used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Gender role theory postulates that society sets norms for what role behaviors are appropriate and the roles that men and women should emphasize: women's proper place is in the home and men's in the workplace [20]. Research on the GRO theory has shown that masculinity traits were related to avowed work role importance, whereas femininity traits to avowed family role importance [21]. This is the work and family role enacting for traditional men and women as decreed in a traditional society.…”
Section: Sex Differences and Gender Diversity In The Work And Family mentioning
confidence: 99%
See 3 more Smart Citations
“…Gender role theory postulates that society sets norms for what role behaviors are appropriate and the roles that men and women should emphasize: women's proper place is in the home and men's in the workplace [20]. Research on the GRO theory has shown that masculinity traits were related to avowed work role importance, whereas femininity traits to avowed family role importance [21]. This is the work and family role enacting for traditional men and women as decreed in a traditional society.…”
Section: Sex Differences and Gender Diversity In The Work And Family mentioning
confidence: 99%
“…However, the demarcation between work and family is blurred for nontraditional men and women as they do not identify with traditional gender traits. For men who identify with nontraditional feminine traits, compared to their traditional counterparts who draw self-identity primarily on the work role, femininity traits make them more sensitive to family-related responsibilities [21]. Powell and Greenhaus [31] found a positive association between femininity traits and the importance of family role for both men and women.…”
Section: Gendered Traits and The Prominence Of Work And Family Role Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The demarcation between work and family, however, is blurred for egalitarian men and women . Egalitarian men equally value work and family life [ 34 ]; thus, when they face increased work demands, they do not opt to sacrifice their family life [ 35 ]. While trying harder to fulfill both roles that are equally akin to their self-identities, they are more likely to overtax the resources and invoke the resource loss spiral.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%